2017
DOI: 10.1111/cfs.12380
|View full text |Cite
|
Sign up to set email alerts
|

Using the RE‐AIM framework to identify and describe best practice models in family‐based intervention development: A systematic review

Abstract: The family unit carries with it a responsibility of possibly being the most important predictor of positive child development. The aim of this systematic review is to identify and describe best practice models or processes in family-based intervention development. The following databases were included in the review: PsychArticles, Academic Search Complete, ERIC, SocIndex, Sage, Sabinet, and Pubmed. Peer-reviewed, English language, qualitative, quantitative, and mixed methods in nature conducted within the last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…As recommended in some studies, it may be useful to discuss any possible external obstacles (timetables and journeys) and internal obstacles (fear of being criticized or questioned) with the family and also expectations of change, as this would clarify the sense of the intervention and its benefits for the family (Gopalan et al, 2010;Small et al, 2015;Sterrett, Jones, Zalot, & Shook, 2010). Other strategies that foster involvement are to more openly emphasize family strengths, resources, and capacities, to revisit the issue of blame, and to set achievable objectives aimed at laying the groundwork for change (Isaacs, Roman, Savahl, & Cheng Sui, 2017;Pereira & Barros, 2018). An initial interview with the family is essential to assessing members' stages of change and to placing the work in the correct context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As recommended in some studies, it may be useful to discuss any possible external obstacles (timetables and journeys) and internal obstacles (fear of being criticized or questioned) with the family and also expectations of change, as this would clarify the sense of the intervention and its benefits for the family (Gopalan et al, 2010;Small et al, 2015;Sterrett, Jones, Zalot, & Shook, 2010). Other strategies that foster involvement are to more openly emphasize family strengths, resources, and capacities, to revisit the issue of blame, and to set achievable objectives aimed at laying the groundwork for change (Isaacs, Roman, Savahl, & Cheng Sui, 2017;Pereira & Barros, 2018). An initial interview with the family is essential to assessing members' stages of change and to placing the work in the correct context.…”
Section: Discussionmentioning
confidence: 99%
“…The focus of the intervention is reflection, understanding the mental states underlying attitudes and behaviours associated with conflicts and developing the capacity to understand oneself and others (Benbassat & Priel, ). Other strategies that foster involvement are to more openly emphasize family strengths, resources, and capacities, to revisit the issue of blame, and to set achievable objectives aimed at laying the groundwork for change (Isaacs, Roman, Savahl, & Cheng Sui, ; Pereira & Barros, ). Due attention should be paid to absences from sessions, which should also be discussed, and consideration could be given to short interventions with a pre‐established duration to facilitate the family's commitment.…”
Section: Discussionmentioning
confidence: 99%
“…Phase 2 was a systematic review aimed at identifying and describing practices and processes used in family‐based intervention development. The findings indicated that most family‐based interventions are strengths‐based, psychoeducative in nature, makes participant engagement and retention a priority, and includes the involvement of the local community (Isaacs, Roman, Savahl, & Sui, ).…”
Section: Methodsmentioning
confidence: 99%
“…Among the more prominent frameworks are the Exploration, Preparation, Implementation, Sustainment (EPIS) framework (Aarons et al, 2010); Getting to Outcomes (Wandersman et al, 2000); the Reach, Efficacy, Adoption, Implementation, and Maintenance framework (Glasgow et al, 1999); and the Active Implementation Frameworks (AIFs; Metz & Bartley, 2012). The way in which these have been utilized ranges from supporting the implementation of RSIs (Barbee et al, 2011; Metz et al, 2015; Pipkin et al, 2013), to structuring the investigation of such interventions (Gannon et al, 2019; Hickey et al, 2018; Moullin et al, 2019), or informing the development of theoretical concepts and models (Isaacs et al, 2017; Mason et al, 2014). While implementation frameworks differ in purpose, content, and form (Albers et al, 2017; Nilsen, 2015), they also have a number of aspects in common, among them the shared assumption that implementation occurs in stages—with two to four stages included in multiple frameworks (Albers et al, 2017).…”
Section: Early Implementationmentioning
confidence: 99%